LECTURERS AND STUDENTS' RECEPTION OF FACE-TO-FACE LEARNING IN THE NEW NORMAL PERIOD - Syaharuddin, Syaharuddin; Jumriani, Jumriani; Noor Handy, M. Rezky; Hidayat Putera, M. Adhitya; Ridha Ilhami, M.; Rusmaniah, Rusmaniah; Agustina, Ella (JURNAL SOCIUS, 2023)
This study aims to describe the acceptance of lecturers and students towards the implementation of face-to-face learning during the new normal period, to analyze the reasons for choosing learning methods, as well as their acceptance and expectations of face-to-face learning. Data collection was carried out through structured interviews using Google Forms with 15 lecturers and 35 students from the Department of Social Sciences FKIP ULM. The results showed that most lecturers preferred online learning (84%), while students were almost balanced between online (54%) and offline (46%) methods. The majority of lecturers choose online learning because of the pandemic, while some students prefer face-to-face because it is considered effective. The study recommends implementing the hybrid learning model while adhering to health protocols and infrastructure requirements according to the Circular Letter of the Director General of Higher Education, Ministry of Education and Culture Number 4 of 2021.